Violent Trauma, Culture, and Power : An Interdisciplinary Exploration in Lived Religion - Walsh, Michelle (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is an interdisciplinary exploration of the intertwining impact of violent trauma, culture, and power through case studies of two ministries serving in different demographic contexts within the United States. Mass shootings continue to rise in the United States, including in religious and school contexts, and the U.S. also is ground zero for the now international Black Lives Matter movement. The author shows how all forms of violent trauma impact more than individuals -devastating communal relationships and practices of religious or spiritual meaning-making in the aftermath, and assesses how these impacts differ according to lived experiences with culture and power. Looking at the two ministries, an urban grassroots lay ministry organization that serves surviving family members in the aftermath of homicide, and a denominational ministry that served a church in the aftermath of a political and religiously motivated shooting, the author develops trauma-specific interdisciplinary tools for lived religion studies.
Keywords: Social sciences.; Gender identity -- Religious aspects.; Ethnology.; Religion and culture.; Religion and sociology.; Psychology and religion.; elektronické knihy; electronic books